Motives for participation in halal food standard implementation: an empirical study in Malaysian halal food industry - Jaswir, Irwandi; Sari, Dian Permata; Che Daud, Mohd Radzi; Sukmana, Raditya (Emerald, 2023)
Purpose This study aims to identify the factor that could be able to motivate the food industry to take part in the standardization process and analyse which motive is the most influential one. This study also examines the relationship between the motive and the implementation itself.